2017
DOI: 10.2514/1.b36390
|View full text |Cite
|
Sign up to set email alerts
|

Method for Determining Nozzle-Throat-Erosion History in Hybrid Rockets

Abstract: The authors of this paper introduce a new reconstruction technique titled Nozzle Throat

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 10 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Kamps et al recently introduced a method, titled the "Nozzle Throat Reconstruction Technique (NTRT)," for determining both A t and ξ histories through the data reduction of commonly measured experimental values with the aim of enabling hybrid rocket researchers to accurately and cost-effectively investigate nozzle erosion experimentally [26]. The two governing equations of this method are the thrust equation shown by (1), and the characteristic exhaust velocity equation shown by (2):…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Kamps et al recently introduced a method, titled the "Nozzle Throat Reconstruction Technique (NTRT)," for determining both A t and ξ histories through the data reduction of commonly measured experimental values with the aim of enabling hybrid rocket researchers to accurately and cost-effectively investigate nozzle erosion experimentally [26]. The two governing equations of this method are the thrust equation shown by (1), and the characteristic exhaust velocity equation shown by (2):…”
Section: Methodsmentioning
confidence: 99%
“…where ∆t represents the sampling rate of the experimental measurement history in s, and t b is the burn time in s. Burn time is defined as the duration of time from the moment the (gauge) chamber pressure reaches 10% of the maximum value to the time at the aft-bisector of the pressure drop at the end of burning. This designation is outlined in [31] (p. 459), and was used in [26,27]. The fuel port radius in Equation 9is calculated based on the fuel mass, M fu , fuel density, ρ fu , and the outer diameter and length of the fuel, D fu and L fu¬ , according to Equation 11:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The third technology is the use of an erosion-resistant material at the nozzle throat. For example, Kamps et al reported that coating the throat of a conventional graphite nozzle with SiC prevented erosion completely in a five second firing test [43]. D'lia et al [44] and Whitmore et al [45] achieved erosion reduction in longer firing durations using throat inserts made of customized erosion-mitigating materials with varying degrees of success.…”
Section: Technologies For Reducing O/f Shift and Nozzle Erosionmentioning
confidence: 99%